Congenital Insensitivity to Pain with Anhidrosis (CIPA): A Case Report - Safari, A (Kowsar, 2011)
Congenital insensitivity to pain with anhidrosis (CIPA) is a rare disorder characterized by episodes of fever and the inability to sense of pain despite the fact that all other sensory modalities remain intact or minimally impaired. The patient also may exhibit the signs of self-mutilation, mental retardation and little or no perspiration. We present a 10 years old Iranian patient diagnosed with CIPA with the above-mentioned clinical characteristics. The prosthetic treatment and the subsequent six month follow-up are discussed. Follow-up of the patient revealed that, with the use of this prosthesis, the patient’s oral function and esthetics were established and the mouth lesions improved. Therefore especial dental management of CIPA patients according to their mental status, age, oral and dental condition is essential for solving the specific problems each case may present and the full mouth teeth extraction should be considered as the last treatment.